Pregnant Women's Experiences in Maintaining Mental Health During Pregnancy in Pontianak City - Litaqia, Wulida; Harmita, Devi; Saputra, Dikki; Luthfi, Muhammad; Najib Febrya Rahman, Ainun (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Maternal mental health is a crucial aspect that affects both maternal and fetal well-being. This study aims to explore the experiences of pregnant women in maintaining their mental health during pregnancy in Pontianak City. Using a phenomenological qualitative approach, six participants were interviewed in-depth to understand the challenges faced and the coping strategies employed. The findings indicate that pregnant women experience anxiety related to childbirth, physical changes, and social pressures. Support from partners, family, and healthcare professionals plays a vital role in maintaining their mental health. Additionally, coping strategies such as relaxation activities, information-seeking, and spiritual approaches are utilized to manage stress. These findings highlight the need for social support-based interventions and mental health education for pregnant women.